A novel strategy to prepare COFs based BN co-doped carbon nanosheet for enhancing mechanical performance and fire safety to PVA nanocomposite. (1st October 2020) - Mu, Xiaowei; Cai, Wei; Xiao, Yuling; He, Lingxin; Zhou, Xia; Wang, Hui-Juan; Guo, Wenwen; Xing, Weiyi; Song, Lei
Abstract: N doped carbon nanosheet and B N co-doped carbon (BNC) nanosheet are first prepared through exfoliation of carbon of Schiff based covalent organic frameworks (COFs) under ultrasound using sodium lignin sulfonate as the intercalation agent and modifier. Then poly (vinyl alcohol) (PVA)/BNC nanocomposite with enhanced thermal oxidation stability, good mechanical performances and enhanced flame retardancy has been prepared through solution blending. The temperature at 5 wt% weight loss and peak heat release rate of PVA loaded with 4 wt% of BNC nanosheet increase by 31.9 °C and 57.3% compared with that of untreated PVA, respectively. A new fire hazard evaluation system based on analytic hierarchy process (AHP) is raised to comprehensively estimate fire risk of prepared sample. It is deduced from AHP that PVA loaded with 4 wt% BNC nanosheet shows the lowest fire risk (77.9 score). The effect of BNC nanosheet on pyrolysis mode of PVA in gaseous and condensed phase has also been investigated to figure out the reason for low fire risk of treated PVA. Graphical abstract: Image 1 Highlights: A novel strategy to prepare B and N doped carbon nanosheet derived from covalent organic frameworks. The PVA/BNC nanocomposite with enhanced thermal oxidation stability and enhanced flame retardancy has been prepared. A new fire hazard evaluation system based on analytic hierarchy process (AHP) is raised. The effect of NBC nanosheet on pyrolysis mode of PVA in gaseous and condensed phase has been investigated.